ANALYSIS OF MENTAL WORKLOAD WITH INTEGRATING NASA TLX AND FUZZY METHOD - Riono Riono; Suparno Suparno; Adi Bandono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
ABSTRAK In carrying out its main duty as a guardian of the territorial water sovereignty republic Indonesia, the strength of the Navy is directed as a strategic force developed under the SSAT. The strength of the Navy can be measured by the arsenal and the quality of the personnel who are responsible for it. The performance, quality of personnel is strongly influenced by the work load it receives. Measurement of personnel workload in Indonesian Warship to determine the class of his current position using the Factor Evaluation System (FES) method that is more oriented on the volume of work and work time. While the mental workload has not been accommodated in the measurement of workload using this method. In this research will carry out the measurement of mental workload of Indonesian Warship personnel for each type of work when the Indonesian Warship operates, using the NASA TLX method integrated with the Fuzzy method. The questionnaire data collection was obtained from 82 respondents Indonesian Warship personnel. From the research results obtained data that of 11 (eleven) types of work in Indonesian Warship at the time of operation, Main Engine Operators work is the work that has the highest mental workload with a value of 74.33. While the type of work that most low-level mental work is to electronics Operators with a value of 58.83. Keywords: Workload, NASA TLX, FUZZY Method, FES